Preparing Islamic Human Resources Competencies as Generation of Digital Bankers in Polytechnics Vocational Education - Marlya Fatira; Anriza WitI Nasution; Ismi Affandi (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The development of the 4.0 industrial revolution is now increasingly real and has an impact on all aspects of human life. Human behavior in carrying out activities for their lives is done digitally. This situation has made all industries including the banking industry adapt to provide the best service to customers through digital service transactions. The need for young professionals of digital bankers is a necessity in the present, therefore vocational colleges are in the form of Polytechnics such as Politeknik Negeri Medan. The Islamic banking and finance study program as at Politeknik Negeri Medan, now need to make adjustments to the preparation of sharia human resources as a generation of digital bankers through the Islamic banking industry through graduate competency can be in accordance with the current needs of the labor market. This study describes the views of alumni from who have worked in Islamic banking. The alumnies explain the competencies needed and are required to have them as bankers in the current digital era. Data collected is primary data obtained through in-depth interviews with informants as many as 4 people. The information received is then analyzed with the conditions in the study program curriculum at the islamic banking and finance study program. Then analyzed to courses, teaching method. Research result that the study program must be prepared alumni to be digital bankers are competencies in the understanding of Islamic bank transaction agreements, competencies as tellers and sharia bank customer service, competence as analysts Islamic bank financing, competency as funding officer and financing officer of Islamic banks. Providing a curriculum that is in accordance with SKKNI, provides courses with the latest content and with learning methods that are tailored to practical needs with current cases. Submission of the learning method is accompanied by the practice of each course as much as a minimum of 50%.